The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.2147/ijgm.s157335
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric traits in patients with vasovagal and unexplained syncope

Abstract: PurposeSyncope is a common condition affecting almost one-third of the general population. The present study measures the prevalence of psychiatric traits in patients presenting with syncope (unexplained and vasovagal) and whether recurrent attacks have an impact on psychiatric profiles.Patients and methodsThis is a case–control study in a tertiary hospital enrolling all patients aged ≥12 years with single or recurrent syncopal attacks. A self-reporting psychometric questionnaire (The Symptoms Checklist-90-Rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Increased event frequency, or syncopal recurrence during follow up, are associated with reduced quality of life in both physical and mental health domains in patients with VVS. Syncopal recurrence is also more common in patients with VVS who have concurrent psychiatric disorders ( 29 ), and conversely, patients who report more frequent syncopal events, are more likely to have a concurrent psychiatric disorder or psychiatric symptoms ( 62 , 63 ). Whether psychological distress predisposes to syncope in susceptible individuals, or whether syncope contributes to psychological distress, is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Increased event frequency, or syncopal recurrence during follow up, are associated with reduced quality of life in both physical and mental health domains in patients with VVS. Syncopal recurrence is also more common in patients with VVS who have concurrent psychiatric disorders ( 29 ), and conversely, patients who report more frequent syncopal events, are more likely to have a concurrent psychiatric disorder or psychiatric symptoms ( 62 , 63 ). Whether psychological distress predisposes to syncope in susceptible individuals, or whether syncope contributes to psychological distress, is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…However, a statistically significant difference for somatization disorder was found between the groups. In the same study, a subanalysis of the case group showed that patients with six or more syncopal episodes had higher rates of depression, anxiety, and somatization disorder compared with those with lesser syncopal attacks (Alhuzaimi et al, 2018). In another study, Giada et al (2005) reported that they found psychopathology in 71% of patients with vasovagal syncope, with a prevalence of somatization disorders (29%), anxiety disorders (28%), and mood disorders (18%).…”
mentioning
confidence: 87%
“…Less commonly encountered cardiacoriginating syncope indicates a serious health concern (Massin et al, 2007;Yeh, 2015). Alhuzaimi et al (2018) compared patients with syncope in the adult age group with a control group and found no difference between the groups in terms of depression, anxiety, and phobia. However, a statistically significant difference for somatization disorder was found between the groups.…”
mentioning
confidence: 99%
“…The relevance of clinically studying, investigating, preventing, and controlling this condition lies in its adverse impact on the affected individual. Atici et al (9), Ng et al (10), and Alhuzaimi et al (11) evaluated the relationship between clinical manifestations, psychological conditions, and quality of life of patients with VVS. They showed that the total number of syncopal episodes is positively and significantly associated with higher levels of distress, anxiety, depression, other somatization types, and low quality of life, especially in recurrent syncope (Figure 1) (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%